Mediating Role of Customer Satisfaction on The Relationship Between Perceived Value and Perceived Service Quality toward Repurchase Intention - Maskudi, Maskudi; Karsiati, Karsiati (Faculty of Economics and Business UNTAG Semarang, 2024)
This study aims to analyze the influence of perceived value and perceived service quality on repurchase intention, as well as the mediating influence of customer satisfaction. This research is a cross-sectional study with a quantitative approach. There were 100 respondents in this study, taken using a purposive sampling technique. Statistical analysis uses multiple linear regressions. The research results show that there is a significant and positive influence of perceived value and perceived service quality on customer satisfaction. The findings further explain that customer satisfaction can mediate the influence of perceived value and perceived service quality on repurchase intentions. Online transportation providers need to focus on perceived value, and perceived service quality felt by customers so that customers will return to be loyal to the company.